Biportal Endoscopic Intramedullary Debridement for Management of Tibial Osteomyelitis - Tun Hing Lui, M.B.B.S. (HK), F.R.C.S. (Edin), F.H.K.A.M., F.H.K.C.O.S.; Ka Kin Cheung, M.B.B.S. (HK), F.R.C.S. (Edin), F.H.K.A.M., F.H.K.C.O.S.; Sze Ying Chan, M.B.ChB. (Arthroscopy Techniques)
Chronic osteomyelitis occurs if the bone infection persists for more than 6 weeks. The presence of dead bone (sequestrum) and intramedullary abscess with chronic infected tissue may protect bacteria from the endogenous host immune response and limit the effectiveness of many antibiotics. Classically, removal of infected tissue inside the medullary cavity requires extensive osteotomy to create a bone window of adequate size. Bone endoscopy (medulloscopy) provides a minimally invasive approach to the medullary cavity of long bones. The purpose of this Technical Note is to describe the details of uniportal endoscopic intramedullary debridement for management of tibial osteomyelitis.